Evolution, cognition, and the history of religion: festschrift in honour of Armin W. Geertz - Klostergaard Petersen, Anders; Gilhus, Ingvild Sælid; Martin, Luther H.; Jensen, Jeppe Sinding; Sørensen, Jesper; Geertz, Armin W. (Supplements to method and theory in the study of religion, 2018)
Intro -- Contents -- List of Figures -- Notes on Contributors -- Preface. A Call for a New Synthesis -- Part 1: The Evolution, Cognition and History of Armin W. Geertz -- Chapter 1. Armin W. Geertz: A Genuine PhD (Puritan, Hippie, and Doctor) - A Man and His Mission -- Part 2: Evolution -- Chapter 2. Why Cultural Evolutionary Models of Religion Need a Systemic Approach -- Chapter 3. The New Collaborative Scientific Study of Religious History -- Chapter 4. Continuity as a Core Concept for a Renewed Scientific Study of Religion -- Chapter 5. Behaviors and Environments: Patterns of Religious World Habitation -- Chapter 6. ``Where is the Future for the Study of Religion?'' On Consilience, Anomalous Monism and a Biocultural Theory of Religion -- Chapter 7. An Old Methodenstreit Made New: Rejecting a `Science-Lite' Study of Religion -- Chapter 8. Making Evolutionary Science of Religion an Integral Part of Cognitive Science of Religion -- Chapter 9. Self-Programming and the Self-Domestication of the Human Species: Are We Approaching a Fourth Transition? -- Chapter 10. The Evolutionary Loop: Archaic Trends in Modern Time -- Chapter 11. Religion as an Artifact of Selection Pressures to Make Hominins More Social -- Chapter 12. The Origin of Religion: Recent Scientific Findings -- Chapter 13. The Meaning of Ritual: Or What a Philosophy of Religion Should Take Into Account -- Chapter 14. Mind the Text: Traces of Mental States in Unstructured Historical Data -- Part 3: Cognition -- Chapter 15. Bridging the Gap: the Cognitive Science of Religion as an Integrative Approach -- Chapter 16. Causality, Deconstruction, and an Unsettling Possibility -- Chapter 17. Politics of Nostalgia, Logical Fallacies, and Cognitive Biases: the Importance of Epistemology in the Age of Cognitive Historiography -- Chapter 18. Scientific Worldview Studies: A Programmatic Proposal